The effect of light quality and quantity on carbon allocation in Chromera velia - Lukeš, Martin; Giordano, Mario; Prášil, Ondřej (Folia microbiologica, 2019)
Chromera velia is a marine photosynthetic relative of human apicomplexan parasites. It has been isolated from coral reefs and is indicted for being involved in symbioses with hermatypic corals. C. velia has been subject to intensive research, but still very little is known of its response to light quality and quantity. Here, we have studied the growth and compositional responses of C. velia to culture under monochromatic light (blue, green or red), at two photon flux densities (PFD, 20 and 100 μmol photons m-2 s-1). Our results show that C. velia growth rate is unaffected by the quality of light, whereas it responds to PFD. However, light quality influenced cell size, which was smaller for cells exposed to blue monochromatic light, regardless of PFD. PFD strongly influenced carbon allocation: at 20 μmol photons m-2 s-1, carbon was mainly allocated into proteins while at 100 μmol photons m-2 s-1, carbon was allocated mainly into carbohydrate and lipid pools. The blue light treatment caused a decrease in the lipids and carbohydrates to proteins and thus suggested to affect nitrogen metabolism in acclimated cells. Whole-cell absorption spectra revealed the existence of red-shifted chlorophyll a antenna not only under red light but in all low PFD treatments. These findings show the ability of C. velia to successfully adapt and thrive in spectrally very different environments of coral reefs.
Keywords: chlorofyl a; Light; Carbon; Photosynthesis; fotosyntéza; světlo; Chlorophyll A; Alveolata; uhlík